Status of Children Born Out of Wedlock: A Study of Constitutional Court Decision and Its Relevance to the View of Ibnu Taimiyah - Ali, Bukhari; Wulandari, Nur; Erianti, Nahara (El-Usrah: Jurnal Hukum Keluarga, 2024)
The Constitutional Court Decision No. 46/PUU-VIII/2010 has introduced a new paradigm in the civil and family law systems. However, this decision has faced significant controversy among Muslims, who constitute the majority religious group in Indonesia. The majority of ulema (Muslim scholars) maintain that children born from zina (fornication) cannot be attributed to their biological fathers. In contrast, Ibn Taimiyah, a renowned Islamic scholar, has proposed the concept of istilhaq, which allows for the attribution of children born from zina to their fathers. This study aims to address three research questions: 1) What is the content of the Constitutional Court Decision No. 46/PUU-VIII/2010? 2) What is Ibn Taimiyah’s opinion on children born out of wedlock? 3) What is the relevance of the Constitutional Court decision to Ibn Taimiyah’s opinion? The study employed a juridical-theoretical method, utilizing both legal and Islamic perspectives. The findings reveal that the majority of ulema hold the view that children born out of wedlock are only attributed to their mothers. Ibn Taimiyah, on the other hand, argues that they can be attributed to their biological fathers through the concept of istilhaq (acknowledgment) and qiyafah (facial resemblance). The Constitutional Court decision does not provide a definitive clarification on the status of children born out of wedlock. Consequently, both children born from underhand marriages and from zina become the responsibility of the biological fathers if their paternity can be established through DNA testing. The relevance between the Constitutional Court decision and Ibn Taimiyah’s opinion lies in their shared recognition of the possibility of establishing nasab (lineage) without solely considering the circumstances of the child’s birth. This recognition can be achieved through DNA testing in the present era and through acknowledgment and facial resemblance assessments in Ibn Taimiyah’s time.